Avoiding an "Unavoidably Imperfect Situation": Searching for Strategies to Divert Mentally Ill People Out of Immigration Removal Proceedings - Molly Bowen (Washington University Law Review, 2012)
Recent efforts to better protect mentally ill individuals in removal proceedings have focused on increasing procedural safeguards, such as providing free attorneys, releasing medical records in government custody, and training immigration judges on mental health symptoms. The goal of these reforms is to ensure that all individuals receive a full and fair hearing. In May 2011, the Board of Immigration Appeals advanced this call for due process protections in Matter of M-A-M-, which for the first time required immigration judges to assess mental competency of individuals in immigration removal proceedings. These procedural reforms, however, are insufficient to stop wrongful removals of mentally ill people. This Note argues that the focus must shift from simply increasing procedural rights to developing options to divert mentally ill individuals out of immigration removal proceedings altogether. This Note presents the unique challenges facing mentally ill individuals in immigration removal proceedings and the lack of tailored protections in the current system. It explores how Matter of M-A-M- presents a limited improvement to the current system. Finally, it presents two pathways out of immigration removal proceedings, termination and prosecutorial discretion, and offers recommendations for strengthening these options.
Keywords: Matter of M-A-M; mentally ill; removal proceedings; wrongful removals